Variation and Relationship of Selected Wood Properties in Planted Kelempayan (Neolamarckia Cadamba (Roxb.) Bosser) - Jusoh, Ismail (1993)
The tall and straight bole of Kelempayan (Neolamarckia cadamba (Roxb.) Bosser), a fast-growing indigenous species, has the potential to be used for forest plantation species. This study was carried out to evaluate the inherent properties of the wood. Six planted trees under similar site conditions were sampled along their radii and at five different height levels to evaluate the inherent variation of wood and the influence of anatomical properties on its specific gravity (SG) and bending strength. Over all me ans for SG was 0.36, green moisture content 174.83 percent (%), tangential shrinkage 6.46%, radial shrinkage 3.28% and volumetric shrinkage 9.90%. The overall means for modulus of elasticity ( MOE) and modulus of rupture {MOR ) were 7667 and 71 megapascal (MPa) respectively. Vessel comprised 16.69% of wood, ray 11.96% and fibre 71.41%. Fibre length averaged 1.38 millimeter, fibre diameter 35.01 microns, fibre lumen diameter 24.82 microns and fibre wall thickness 5.11 microns. These physical and mechanical properties are similar to many other light hardwoods species, indicating the suitability of wood for general utility timber.